EFFECTIVENESS AND EFFICIENCY OF COMMUNITY-BASED FOREST MANAGEMENT IN HOANG LIEN NATIONAL PARK, LAO CAI PROVINCE - Ha Anh, Nguyen; Thi Thu Ha, Tran (Journal of Forestry Science and Technology, 2017)
Community-based forest management (CBFM) is a strategy aiming to improve livelihoods of forest user, reduce poverty, conserve natural resources, and promote good governance and decentralization by increasing the role of local people in governing and managing forest resources. Since 2004, Vietnam has started to adopt CBFM as an important land-use policy and applied in several mountainous areas, mostly for areas which have National Park. This study aims at assessing the efficiency and effectiveness of CBFM implementation in Hoang Lien National Park, Lao Cai province. The results showed that the current CBFM implementation in Hoang Lien National park is receiving more attention from local community than before. However, the participation of community just reaches moderate level associated with low educational and income level or local awareness of forest resources, which are the factors that influence CBFM efficiency and effectiveness. Solutions are also recommended and focus on raising local awareness to enhance people’s participation, increasing human resource capacity for management and supporting local incomes.